A referenciação em textos verbo-imagéticos - Silva, Walleska Bernardino (2014)
This research has the main object to analyze the referential operation of objects of discourse in verb-imagery texts. Thereto, the theoretical validity is incumbent on the postulates of Textual Linguistics with social cognitive discourse basis, specially the referenciation (MONDADA; DUBOIS, 2003), by the referential approach and non-contextual mention (CAVALCANTE, 2011). The principles and categories of analysis of this approach are correlated to the model theory of context by Van Dijk (2012), for the observation of the operation of objects of discourse in 22 verb-imagery texts present in two different genres: the strip and the advertisement. The study shows that is possible to extend the categories of referential processing used in verbal texts into texts which commune, in its materiality, by word and image in a way that the principles which sustain the referenciation while a negotiated (re)building from objects of discourse keep itself assured. It still evinces that all the analytical categories of referenciation through the non-mention approach are contemplated in all the verb-imagery texts, preferably the referential introduction and direct anaphora, made by objects of discourse in verbal and imaging manner. The recategorization is confirmed as a phenomenon that surpasses all the referential processing, mainly performed by objects of discourse in the imaging manner. Linked by this finding, the preference by the argumentative orientation of referential processing is verified, since the analysis demonstrate that the same object of discourse can be observed in more than one reference category and assuming more than one role, stating the principle that deals with the simultaneous roles of referential processing as well as referential accessibility.